Pressure distribution in a porous squeeze film bearing lubricated with a Herschel-Bulkley fluid - Walicka, Anna; Jurczak, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
The influence of a wall porosity on the pressure distribution in a curvilinear squeeze film bearing lubricated with a lubricant being a viscoplastic fluid of a Herschel-Bulkley type is considered. After general considerations on the flow of the viscoplastic fluid (lubricant) in a bearing clearance and in a porous layer the modified Reynolds equation for the curvilinear squeeze film bearing with a Herschel-Bulkley lubricant is given. The solution of this equation is obtained by a method of successive approximation. As a result one obtains a formula expressing the pressure distribution. The example of squeeze films in a step bearing (modeled by two parallel disks) is discussed in detail.
Keywords: Herschel-Bulkley lubricant; porous bearing; squeeze film; thrust bearing